2020
DOI: 10.1002/adsc.202000786
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Boronated γ‐Lactams via Palladium‐Catalyzed Intramolecular Boryldifluoroalkylation of Alkenes

Abstract: An approach for the preparation of boronated γ-lactams via palladium-catalyzed boryldifluoroalkylation of alkenes with α-bromodifluoroacetamides was developed. This method exhibits good functional group tolerance. Various boronated products were obtained in moderate to good yields for 1 h. Mechanistic studies indicated that this reaction may involve an intramolecular radical cascade cyclization process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Finally, the intermediates B were captured by diselenides 52 to further generate the target products 53 and selenyl radicals, which can be converted into R 2 SeBr depending on the reduction of Cu(II) to Cu(I) [25]. In 2018 and 2020, the research groups of Mai, Lu, and Liu developed a practical access to the synthesis of 4-benzyl-α,α-difluoro-γ-lactams 60 or 4-boronated α,α-difluoro-γ-lactams 63 by the reactions of α-bromodifluoroacetamides 58 or 61 with arylboronic acids 59 or B 2 pin 2 62 using Ni(OTf) 2 or Pd(PPh 3 ) 4 as catalyst (Scheme 12) [27,28]. A series of arylboronic acids 59 bearing various substituents such as 3-CH 3 CO, 3,5-dimethoxy, 4-CO 2 Me, 3-CO 2 Et, 4-BocNH, 4-CH 3 SO 2 , 4-t-Bu, 4-F, 3-CH 3 , 4-Cl, and 4-CF 3 , were examined to react with α-bromodifluoroacetamides 58 containing different aryl groups on the N atom to afford the desired products 4-benzyl-α,α-difluoro-γ-lactams 60 in 57%-94% yields catalyzed by Ni(OTf) 2 , ligand L, and PPh 3 in the presence of K 2 CO 3 as base in 1,4-dioxane at 80 C for 8 h [27].…”
Section: From α-Bromodifluoroacetamides With Diselenides or Disulfidesmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, the intermediates B were captured by diselenides 52 to further generate the target products 53 and selenyl radicals, which can be converted into R 2 SeBr depending on the reduction of Cu(II) to Cu(I) [25]. In 2018 and 2020, the research groups of Mai, Lu, and Liu developed a practical access to the synthesis of 4-benzyl-α,α-difluoro-γ-lactams 60 or 4-boronated α,α-difluoro-γ-lactams 63 by the reactions of α-bromodifluoroacetamides 58 or 61 with arylboronic acids 59 or B 2 pin 2 62 using Ni(OTf) 2 or Pd(PPh 3 ) 4 as catalyst (Scheme 12) [27,28]. A series of arylboronic acids 59 bearing various substituents such as 3-CH 3 CO, 3,5-dimethoxy, 4-CO 2 Me, 3-CO 2 Et, 4-BocNH, 4-CH 3 SO 2 , 4-t-Bu, 4-F, 3-CH 3 , 4-Cl, and 4-CF 3 , were examined to react with α-bromodifluoroacetamides 58 containing different aryl groups on the N atom to afford the desired products 4-benzyl-α,α-difluoro-γ-lactams 60 in 57%-94% yields catalyzed by Ni(OTf) 2 , ligand L, and PPh 3 in the presence of K 2 CO 3 as base in 1,4-dioxane at 80 C for 8 h [27].…”
Section: From α-Bromodifluoroacetamides With Diselenides or Disulfidesmentioning
confidence: 99%
“…A plausible mechanism for the synthesis of 4-boronated α,α-difluoro-γ-lactams 63 was proposed by Liu and co-workers, as shown in Scheme 13 [28]. First of all, the interaction of Pd(0) with α-bromodifluoro acetamides 61 generated Pd(I)X and radical intermediates A, which were rapidly converted into the intermediates B through an intramolecular cyclization.…”
Section: From α-Bromodifluoroacetamides With Diselenides or Disulfidesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these reports are restricted by the relatively narrow scope of substrates. In recent years, an increasing interest in radical cyclization reactions has led to the development of efficient protocols to synthesize various functionalized α,α-difluoro-γ-lactams through radical-mediated processes. For instance, radical cascade cyclization of alkenes catalyzed by transition metals, such as copper, nickel, and palladium, was developed to rapidly assemble CF 2 -decorated γ-lactams. Furthermore, Zhu et al demonstrated a novel photoredox/iodide catalytic system toward these compounds via aminodifluoroalkylation of alkenes (Scheme a1) .…”
Section: Introductionmentioning
confidence: 99%